Serum Therapy for Tuberculosis Revisited: Reappraisal of the Role of Antibody-Mediated Immunity against Mycobacterium tuberculosis - Glatman-Freedman, Aharona (American Society for Microbiology, 1998)
Fifty years after the introduction of the first effective antimicrobial agents against Mycobacterium tuberculosis, this pathogen continues to be a tremendous public health problem. The rise in the number of resistant strains and the difficulties involved in the therapy of tuberculosis in immunocompromised AIDS patients have renewed the interest in the development of effective vaccines. To evaluate whether a potential vaccine against tuberculosis could prevent infection by eliciting a protective antibody response, we reviewed the history of antibody-mediated immunity against tuberculosis. Review of the literature of the past 100 years demonstrates that there is sufficient evidence to conclude that antibody-mediated immunity can modify the course of infection in certain situations. Based on our findings and on what is known in other systems, we propose that the role of antibody-mediated immunity to M. tuberculosis be reexamined, using advanced technology.